THEORETICAL ANALISYS OF THE CONCEPT “SOLIDARITY” AND ITS REFERENCE TO ACADEMIC DISCOURSE - Mirra, Carl; Fedorenko, Svitlana (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The paper focuses on the theoretical analysis of the essence of the concept “solidarity” and its relationship to the academic context. For this purpose, the philosophical and sociological approaches towards defining “solidarity” are explored; the conceptual components of solidarity, such as moral values, ethical obligations, desire for transformations and care as a moral and ethical value, are enlarged upon; and the impact of solidarity on the enhancement of academic environment is considered. In the study, the following theoretical methods were exploited: analysis and synthesis – to formulate the initial provisions of the paper; study and systematization of primary sources on the issue under scrutiny. It is stated that solidarity is not a static phenomenon, but an extremely multifaceted, interdisciplinary and dynamically developing one. Solidarity includes moral, political and social elements, which are also supported by organizational infrastructure and institutional frameworks. It is stressed that the concept of solidarity has become increasingly used in curricula and pedagogical literature over the past two decades, particularly by scholars who focus on civic education for social and political change. The conscious nature of solidarity contributes to the fact that the normative foundations of any community, in particular the educational one, determine such social characteristics as the ability to self-restraint and discipline, as well as the compatibility of individual interests, feelings and experiences. It is concluded that In the scientific discourse, the concept of “solidarity” is viewed as it follows: firstly, as integration based on the common interests of individuals, groups, as well as interdependence and responsibility for something; secondly, as unity based on the moral values, ethical obligations and care as a result of adherence to common norms and values; and thirdly, as a joint activity to achieve a certain goal, i. e., mutual assistance in accordance with the principle of “one for all and all for one.” The theoretical significance of the paper lies in expanding the existing understanding of the concept “solidarity” into the academic context.